1147. Pseudo-Outbreak of Clostridium paraputrificum Related to Anaerobic Tent Contamination. (26th November 2018) - Mitchell, Kaitlin; Rece, Luann; Duster, Megan; Shirley, Daniel; Safdar, Nasia; Chen, Derrick
Abstract: Background: Over a 2-month period, eight patient cultures in our clinical microbiology laboratory were positive for Clostridium paraputrificum, an uncommon spore-forming microbe. The possibility of a pseudo-outbreak related to contamination in the laboratory's anaerobic tent was considered. Methods: This study occurred at a 505-bed tertiary care university-affiliated teaching hospital. Patient samples were cultured and evaluated following standard protocols, and isolates of C. paraputrificum were identified using matrix-assisted laser desorption ionization-time of flight mass spectrometry (MALDI-TOF MS). To identify additional cases, MALDI-TOF MS testing reports were manually reviewed and matched to patient records. Concurrently, the laboratory's anaerobic tent was sampled after cleaning with isopropyl alcohol (and later with bleach or sporicidal disinfectant) following standard procedures and protocols recommended by the tent manufacturer (Coy). Pulsed-field gel electrophoresis (PFGE) was performed on isolates from patients ( n = 8) and the anaerobic tent ( n = 6). Results: Despite cleaning with isopropyl alcohol or bleach, surface samples from the anaerobic tent grew C. paraputrificum . PFGE analysis revealed all patient and anaerobic tent isolates to be indistinguishable, suggesting that they originated from a common source. Growth of the organism from patient samples was therefore regarded as potential contamination. Prior to this, six of the eight patients received antibiotics related to this positive culture and had Infectious Disease consultations. Providers of the patients were contacted regarding the contamination issue. The anaerobic tent manufacturer was consulted and ultimately recommended using Peridox Sporicidal Disinfectant. Six months later, the tent was re-sampled and did not yield positive cultures. Conclusion: A pseudo-outbreak of the uncommon organism C. paraputrificum was related to insufficient disinfection practices of an anaerobic culture tent. This had negative effects on our institution and patient care in terms of cost, time, and unnecessary treatment. The use of sporicidal disinfectant has since proven effective to prevent contamination from spore-producing microbes. Disclosures: All authors: No reported disclosures.